Flexible Platinum(0) Coordination to a Ditungsten Ethanediylidyne. (8th May 2019) - Frogley, Benjamin J.; Hill, Anthony F.
Abstract: The lithiocarbyne [W(≡CLi)(CO)2 (Tp*)] (Tp*=hydrotris(3, 5‐dimethylpyrazol‐1‐yl)borate) reacts with [PtCl2 (L2 )] (L2 =1, 5‐cyclo‐octadiene, norbornadiene) to furnish ditungsten ethanediylidyne complexes, [W2 μ‐C2 Pt(L2 )(CO)4 (Tp*)2 ], wherein a trigonal platinum(0) center unsymmetrically ligates one W≡C bond in the solid state but rapidly shimmies between the two W≡C bonds in solution. The η 4 ‐dienes are displaced by monodentate CO or isocyanide ligands to provide derivatives where both W≡C bonds coordinate to a single Pt 0 center, attended by significant distortion of the WCCW spine. Abstract : An Pt und Au koordiniert : Die Kupplung von zwei μ‐Carbido‐Liganden ergibt ein seltenes Beispiel eines Diwolfram‐Ethandiylidins W≡C−C≡W. Diese Spezies zeigt eine Reihe an ungewöhnlichen Koordinationsmodi zu anderen Metallzentren.